Case Report : Management of Open Pyometra on the Persian Queen - Fadhilla Taqwa, Sultan; Syah, Nanda Yulian (Universitas Airlangga, 2024)
Pyometra commonly occurs in female cats. There are two types of pyometra: open pyometra and closed pyometra. Open pyometra refers to purulent and bloody discharge from the vulva, while closed pyometra does not have any vaginal discharge; however, there is an enlarged abdomen from the fluid-filled uterus. A 2-year-old Persian queen with an enlargement abdomen was clinically diagnosed with open pyometra as there was vaginal discharge. Additional examination, such as ultrasonography, was also performed to establish the diagnosis. Using ultrasonography, hyperechoic imaging clearly showed in the uterine lumen of the uterus. Based on the following examinations, an ovariohysterectomy was performed to eliminate the source of infection. Anti-inflammatory and antibiotic drugs were administered post-surgery, and the patient fully recovered after one week of intensive care.